Photovoltaic Cell with Built-In Antenna for Internet of Things Applications - Ali, Ahmed; Yun, Yeojun; Wang, Heesu; Lee, Keekeun; Lee, Jaejin; Park, Ikmo (IEEE Access, 2021)
A compact and low-profile photovoltaic (PV) cell with a Built-In antenna is proposed for Internet of Things (IoT) applications. The proposed design exploits the gallium arsenide (GaAs)-based PV cell for antenna operation; for this purpose, a hexagonal slot with a trapezoidal perturbation is cut from the active area and bottom contact of the PV cell for resonance. The bottom contact of the PV cell is also used as the ground plane for the antenna. An AC blocking circuit is designed to prevent the flow of RF current toward the PV cell, and a chip inductor is used as an RF choke in the circuit. Thus, a single device simultaneously functions as a PV cell and an antenna. The GaAs PV cell shows a power conversion efficiency (PCE) of 13.25% without antireflection coating, with an open-circuit voltage (Voc), a short-circuit current density (Jsc), and a fill factor (FF) of 0.963 V, 21.00 mA/cm2, and 65.52%, respectively. Furthermore, the optical transparency of the proposed PV-cell antenna is greater than 90%. The complete structure occupies an overall volume of 31.4 mm $×33$ mm $×0.639$ mm ( $0.25λ _{o} × 0.26λ _{o} × 0.0052λ _{o}$ at 2.45 GHz), and the antenna operates in the range of 2.14 to 2.94 GHz, with a gain of 2.8 dBi at 2.45 GHz.
Keywords: Antenna operation; Bottom contacts; Built-in antennas; Compact and low profile; Ground planes; Internet of Things (IOT); Optical transparency; Power conversion efficiencies; Compact antenna; integrated antenna; IoT devices; photovoltaic (PV) cell; slot antenna